Market Hog Project Financial Considerations - Alyssa Schortinghouse; Brian Estevez; Chad Carr; Nicholas Simmons (EDIS)
The aim of this new 6-page document is to introduce the financial considerations for a market hog project, to maximize profits for the project and to demystify the unexpected expenses that are often incurred. Secondarily, this document is designed to serve as a guide in creating a market hog project budget. The audience for this document includes youth interested in or participating in a market hog project, their families, and other interested parties. Written by Alyssa Schortinghouse, Brian Estevez, Chad Carr, and Nick Simmons, and published by the UF/IFAS Florida 4-H Youth Development Program. https://edis.ifas.ufl.edu/4h426